UPAYA PEMERINTAH PERANCIS DALAM MENGHADAPI DAMPAK TERORISME PASCA SERANGAN DI KANTOR MAJALAH CHARLIE HEBDO - Ainun Ardhiwianto (HI 15 UMY 414, 2015)
*414 Charlie Hebdo magazine itself is a unique magazine. Only certain circles who can understand the content of the magazine. But the uniqueness of the stretcher magazine, the content contained in certain topics tend to be rude and insinuated an agency, institution or famous figures. The magazine later issued edition that contains content caricatures of the Prophet Mohammed. This has sparked a lot of anger in the Muslim community of France. The Prophet Muhammad is a very important figure in Islam. He is the messenger of Allah. Face and apparently was never anyone know the details, because Allah always hide the original appearance of the Prophet Muhammad with a view to keeping the prophet that is not created or imitated the shape of his face. But the magazine Charlie Hebdo caricaturing the Prophet Muhammad by inserting the contents of the writing that seemed insulting.